Mortality in sickle cell disease: A population‐based study in an aboriginal community in the Gudalur Valley, Nilgiris, Tamil Nadu, India. Issue 3 (31st December 2020) - Sheshadri, Veena; Shabeer, Pathayakandi; Santhirapala, Vatshalan; Jayaram, Anusha; Krishnamurti, Lakshmanan; Menon, Nandakumar
Abstract: Background: Sickle cell disease (SCD), the most common monogenic disorder, affects more than 300 000 births annually, with 44  000 in India. Although the clinical phenotype of SCD is considered to be milder in aboriginal populations in India, there is a paucity of data on outcomes. To determine the severity of SCD in this population, we studied mortality rates and causes of mortality in a longitudinal cohort of patients with SCD in a remote aboriginal community in India receiving community‐based comprehensive care. Procedures: Causes of death were analyzed in this cohort from January 2008 to December 2018. Details were collected from hospital records and in case of deaths at home by utilizing the WHO verbal autopsy questionnaire. Results: The cohort consisted of 157 patients belonging to the Paniya, Betta Kurumba, Kattunyakan, and Mullu Kurumba tribes. During the study period, there were 22 deaths, all from the Paniya tribe. Twelve deaths (54.5%) occurred in the hospital and the remaining at home (45.5%), reflecting a crude mortality rate of 140 per 1000 population. Twenty‐five percent of deaths occurred in the 6–18 age group. There were no deaths in the 0–5 age group. The median age of death was 25 years, which was 30 years less than in the non‐SCD aboriginal population. The leading causes of death were acute chest syndrome, anemia, and sepsis among the SCD patients and stroke and suicides in the non‐SCD aboriginal population. Conclusion: SCD is a severe disease among the Gudalur Valley's aboriginal population with a significant risk of premature mortality.